Secret historian the life and times of Samuel Steward, professor, tattoo artist, and sexual renegade - Spring, Justin 1962- (New York Farrar, Straus and Giroux, 2010)
Drawn from the secret diaries and journals of novelist, poet, and university professor Samuel M. Steward, this is a reconstruction of one of the more extraordinary hidden lives of the twentieth century. An intimate friend of Gertrude Stein, Alice B. Toklas, and Thornton Wilder, Steward maintained a secret sex life from childhood on, documenting his experiences in vivid (and often very funny) detail. After leaving academe to become tattoo artist Phil Sparrow, Steward worked closely with Alfred Kinsey on his landmark sex research. During the early 1960s, Steward changed his identity once again, this time to write exceptionally literate, upbeat homosexual pornography as Phil Andros. An archive of his papers, lost since his death in 1993, has provided biographer Justin Spring with the material for an illuminating life-and-times biography. More than merely the story of one remarkable man, this is a moving portrait of gay life long before gay liberation.--From publisher description.
First paperback edition 2011
UCWS-2015-G-2415 donated by Emily Ros-Anne Briggs, California USA
Keywords: Steward, Samuel M; Authors, American -- 20th century -- Biography; Poets, American -- 20th century -- Biography; Novelists, American -- 20th century -- Biography; Gay authors -- United States -- Biography; College teachers -- Illinois -- Chicago -- Biography; Tattoo artists -- New York (State) -- New York -- Biography; Sexology -- Research -- United States -- History -- 20th century; Pornography -- United States -- History -- 20th century